Remote Laboratory for Supporting e-Studies in Electronics - Cvjetkovic, Vladimir M; Sulema, Yevgeniya S (International Journal of Online and Biomedical Engineering (iJOE), 2006)
Abstractâ?? E-learning becomes more and more popular today. It gives an opportunity for studying to persons who are not able to attend traditional courses and lectures for some reasons. In areas such as humanities or economical education, E-trainings provide a student with practically the same quality of learning materials. But in case of technical education a student must have traditional laboratory lessons to obtain practical knowledge on the subject. It concerns chemistry, physics, electronics and other technical disciplines. However, modern network technologies allow creating remote laboratories for supporting e-studies. The idea of using the remote lab for support of e-teaching electronics is discussed in the article. The structure and functionality of the remote laboratory are described. The software and hardware parts of the remote lab are considered and presented, as well.